I pluck — contemplating dyeing and ageing through Gray hairs - Terhi Marttila (MatLit)
It was only in my late 30s that I realised that most of the women around me dye their hair. I began to scrutinize my own hair and found many gray hairs amongst my dark brown ones. I started to wonder why women’s gray hair is so invisible. I wrote Gray hairs and realised that to choose not to dye is an act of resistance to both age and gender-based oppression and discrimination. This article is a practitioner reflection on Gray hairs. I begin by contextualizing the work, and then I reflect on some of the comments that people made when I shared Gray hairs with them. Finally, I look at how the visual, process-based elements and interaction through clicking (as plucking) of gray hairs complement the written elements.